2011
DOI: 10.1016/j.biopsych.2011.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral Prefrontal γ-Aminobutyric Acid in Men Predicts Individual Differences in Rash Impulsivity

Abstract: Background-Impulsivity is a multifaceted personality construct associated with numerous psychiatric disorders. Recent research has characterized four facets of impulsivity: 'urgency' (the tendency to act rashly especially in the context of distress or cravings); 'lack of premeditation' (not envisaging the consequences of actions); 'lack of perseverance' (not staying focused on a task); 'sensation seeking' (engaging in exciting activities). Urgency is particularly associated with clinical populations and proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 85 publications
(118 reference statements)
6
108
1
Order By: Relevance
“…Preclinical studies suggest that reductions in or lower levels of GABA are associated with greater impulsivity (Boy et al 2011; Murphy et al 2012; Paine et al 2011). We have previously shown that [ 11 C]Ro15‐4513 is sensitive to GABA levels, and since it is an inverse benzodiazepine agonist, lower levels of GABA would be associated with higher [ 11 C]Ro15‐4513 binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies suggest that reductions in or lower levels of GABA are associated with greater impulsivity (Boy et al 2011; Murphy et al 2012; Paine et al 2011). We have previously shown that [ 11 C]Ro15‐4513 is sensitive to GABA levels, and since it is an inverse benzodiazepine agonist, lower levels of GABA would be associated with higher [ 11 C]Ro15‐4513 binding.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst GABA measured this way is predominantly metabolic in origin (Myers et al 2014; Myers et al 2016b), it is interesting that a lowered magnetic resonance spectroscopy GABA signal ([GABA+]) in HV has in some studies been associated with higher levels of impulsivity. For instance, it has been shown that [GABA+] levels in dorsolateral prefrontal regions negatively correlate with urgency impulsivity (Boy et al 2011); low [GABA+] in perigenual anterior cingulate cortex was associated with greater delay aversion on Cambridge gambling task (Fujihara et al 2015) and higher scores on self‐report Barratt Impulsiveness Scale‐11 in one study (Silveri et al 2013) but not another (Janes et al 2013). Lower [GABA+] in the striatum is associated with poorer impulse control in Go‐NoGo task (Quetscher et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of children with ADHD, lower GABA levels in a region including parts of the primary somatosensory and motor cortices have been reported (Edden et al, 2012). In healthy adolescents and adults, two recent studies showed a negative association of GABA levels in the dorsolateral prefrontal cortex with impulsivity (Boy et al, 2011;Silveri et al, 2013). Despite these studies, Hayes argues that there is still a lack of research on GABA in the general context of impulsivity (Hayes et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…It is characterized by rapid and unplanned reactions to stimuli before thorough processing of information (Arce and Santisteban, 2006). In the DSM (DSM-IV-TR; American Psychiatric Association 2000), impulsivity is the second most frequent symptom (Boy et al, 2011). There is a growing interest in understanding impulsivity among healthy populations as this trait can be interpreted along a dimension, but the underlying mechanisms across the full range have not been clarified yet (Dimoska and Johnstone, 2007;Kam et al, 2012;Stanford et al, 2009).…”
Section: Introductionmentioning
confidence: 99%